A STUDY ON BASIC KNOWLEDGE AND PRACTICES FOR ROAD TRAFFIC SAFETY MEASURES AMONG UNDERGRADUATE MEDICAL STUDENTS OF UTTAR PRADESH - NATH, SOM; KUMAR, SANDEEP; NAQUVI, KAMRAN JAVED; NATH, MANJUSHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were to assess the knowledge and practices of road traffic safety measures among undergraduate medical students and recommendation to prevent road traffic accident. Methods: It was an institutional-based cross-sectional study among undergraduate medical students who knew driving. Total 138 study subjects were purposively selected from three batches. A self-structured questionnaire based on knowledge and practices related to road traffic safety measures with Yes/No answer pattern. Data were collected, compiled, and analyzed using appropriate software. Results: Overall level of knowledge for road traffic safety measures was good/moderate among 37.7% of medical students each while poor among 24.6% students (more among 1st year/39.3% than 2nd year/19.0%, 3rd year/10.0%) (statistically significant X2 =13.304, p-value=0.01). Road traffic safety practices were followed by students (%), namely, wearing a seat belt while driving/seating in four-wheeler’ by 84.1% and neither keep specified speed limit on road/2.9% nor obey all traffic signals/lights/signs’/2.9%. Few students use mobile phone while driving, namely, 2nd year/19.0% and 3rd year/10.0%. Some students “Not Wear Helmet while driving a two-wheeler”/21.7%; “Wrong overtaking from left side”/17.4%; and “drive even when alcoholic”/4.3% of participants. Conclusions: Knowledge for road traffic rules/regulation was good/moderate among average number of students. Majority of medical students’ obey all traffic rules/light signal and signs while some students still did not follow it; use mobile phone while driving/not stop at zebra crossing and neither use indicators while turning nor keep valid DL. To improve the current scenario, road traffic safety rules/measures should be added in our medical curriculum and there is need of frequent awareness campaign related to road safety measures to change their behavior while driving and save their precious life.